Hypoxia induced lactate acidosis modulates tumor microenvironment and lipid reprogramming to sustain the cancer cell survival - Singh, Lakhveer; Nair, Lakshmi; Kumar, Dinesh; Arora, Mandeep Kumar; Bajaj, Sakshi; Gadewar, Manoj; Mishra, Shashank Shekher; Rath, Santosh Kumar; Dubey, Amit Kumar; Kaithwas, Gaurav; Choudhary, Manjusha; Singh, Manjari (Frontiers in Oncology, 2023)
It is well known that solid hypoxic tumour cells oxidise glucose through glycolysis, and the end product of this pathway is fermented into lactate which accumulates in the tumour microenvironment (TME). Initially, it was proclaimed that cancer cells cannot use lactate; therefore, they dump it into the TME and subsequently augment the acidity of the tumour milieu. Furthermore, the TME acts as a lactate sink with stope variable amount of lactate in different pathophysiological condition. Regardless of the amount of lactate pumped out within TME, it disappears immediately which still remains an unresolved puzzle. Recent findings have paved a pathway in exploring the main role of lactate acidosis in TME. Cancer cells utilize lactate in the de novo fatty acid synthesis pathway to initiate angiogenesis and invasiveness, and lactate also plays a crucial role in the suppression of immunity. Furthermore, lactate re-programmed the lipid biosynthetic pathway to develop a metabolic symbiosis in normoxic, moderately hypoxic, and severely hypoxic cancer cells. For instance: severely hypoxic cancer cells enable to synthesize polyunsaturated fatty acids (PUFA) in oxygen scarcity and secrete an excess of lactate in TME. Lactate from TME is taken up by the normoxic cancer cells whereas it is converted back to PUFAs after a sequence of reactions and then liberated in the TME to be utilized in the severely hypoxic cancer cells. Although much is known about the role of lactate in these biological processes, the exact molecular pathways that are involved remain unclear. This review attempts to understand the molecular pathways exploited by lactate to initiate angiogenesis, invasiveness, suppression of immunity and cause re-programming of lipid synthesis. This review will help the researchers to develop proper understanding of lactate-associated bimodal regulations of TME.is, and suppression of immunity.